2017
DOI: 10.1002/cmdc.201700503
|View full text |Cite
|
Sign up to set email alerts
|

Potent Pyrimidine and Pyrrolopyrimidine Inhibitors of Testis‐Specific Serine/Threonine Kinase 2 (TSSK2)

Abstract: Testis-specific serine/threonine kinase 2 (TSSK2) is an important target for reversible male contraception. A high-throughput screen of ~17,000 compounds using a mobility shift assay identified two potent series of inhibitors having a pyrrolopyrimidine or pyrimidine core. The pyrrolopyrimidine 10 (IC50 22 nM; GSK2163632A) and the pyrimidine 17 (IC50 31 nM; ALK inhibitor 1) are the most potent TSSK2 inhibitors in these series, which contain the first sub-100 nanomolar inhibitors of any TSSK isoform reported, ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…A second study by our group (Hao et al, 2004) (Li et al, 2011;Sosnik et al, 2009). In addition, our group and others have developed in vitro assays that have increased the understanding of the TSSKs' mode of regulation (Bucko-Justyna et al, 2005;Hawkinson et al, 2017;Jaleel et al, 2005;Li et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…A second study by our group (Hao et al, 2004) (Li et al, 2011;Sosnik et al, 2009). In addition, our group and others have developed in vitro assays that have increased the understanding of the TSSKs' mode of regulation (Bucko-Justyna et al, 2005;Hawkinson et al, 2017;Jaleel et al, 2005;Li et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…To expand this knowledge, Hawkinson and colleagues applied a HTS screen of around 17,000 compounds using a mobility shift assay with recombinant TSSK2 and fluorescently labeled glycogen synthase (5-FAM-GS) as substrate in a 384-well plate format. These authors were able to identify two, highly potent series of ATP-site TSSK2 inhibitors with either a pyrrolopyrimidine or pyrimidine core [ 82 ]. Three pyrrolopyrimidine core compounds included in this study, with highest potency against TSSK2, had been reported to be also effective inhibitors of several other kinases including IGF-1.…”
Section: Tssk Kinases As Therapeutic Targets For Male Contraceptionmentioning
confidence: 99%
“…While trials of hormonal methods are successful, they come with side effects, such as weight gain, acne, mood changes and changes in libido (39,40). Previous studies demonstrate promising results in targeting TSSKs using kinase inhibitors and the potential application of TSSK allosteric inhibitors (15,41), thereby emphasizing not only the important role of this family of kinases in spermatogenesis, but also how they can be targeted pharmaceutically.…”
Section: Discussionmentioning
confidence: 99%